L'orientation scolaire des mineurs isolés étrangers. L'accompagnement différencié des professionnels de l'enseignement, du travail social et des bénévoles associatifs - Isabelle Rigoni (Les éditions de la Maison des sciences de l'Homme, 2023)
The issue of access to education, schooling and orientation constitutes the junction point of all actors working with unaccompanied foreign minors, whatever their function and status - professional or voluntary. It is also the nerve center which crystallizes heterogeneous points of view, both on the tools to be set up for this public with special educational needs and on orientation issues. Based on a qualitative fieldwork carried out during the 2019-2020 school year in a regional French territory identified for its sharp increase in the number of unaccompanied minors, we propose an analysis of the process of the schooling orientation of these young people, through the prism of the social, academic and more broadly educational treatment reserved for them both by teaching and social work professionals and by the volunteers who support them. After addressing the heterogeneity and specificities of school systems welcoming unaccompanied children, we provide an analysis of the construction of the choices of orientation as proposed by professionals and volunteers of the socio-educational accompaniment.